2022
DOI: 10.3390/v14030516
|View full text |Cite
|
Sign up to set email alerts
|

Apples to Apples? A Comparison of Real-World Tolerability of Antiretrovirals in Patients with Human Immunodeficiency Virus Infection and Patients with Primary Biliary Cholangitis

Abstract: We previously characterized a human betaretrovirus and linked infection with the development of primary biliary cholangitis (PBC). There are in vitro and in vivo data demonstrating that antiretroviral therapy used to treat human immunodeficiency virus (HIV) can be repurposed to treat betaretroviruses. As such, PBC patients have been treated with nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs), alone and in combination with a boosted protease inhibitor or an integrase strand transfer inhibitor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 76 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…Using ligation-mediated PCR and next generation sequencing, we identified HBRV proviral integrations in the biliary epithelium of the majority of PBC patients tested [69] (see NCI Retroviral Integration Database; rid.ncifcrf.gov [90]). In several case series and clinical trials, ART has been shown to improve histological and biochemical outcomes, and reduce viral load with combination ART [56][57][58][59][60]66,67]. Both humoral and cellular immune responses to HBRV have been demonstrated in patients with PBC [46,91].…”
Section: Hbrv and Human Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…Using ligation-mediated PCR and next generation sequencing, we identified HBRV proviral integrations in the biliary epithelium of the majority of PBC patients tested [69] (see NCI Retroviral Integration Database; rid.ncifcrf.gov [90]). In several case series and clinical trials, ART has been shown to improve histological and biochemical outcomes, and reduce viral load with combination ART [56][57][58][59][60]66,67]. Both humoral and cellular immune responses to HBRV have been demonstrated in patients with PBC [46,91].…”
Section: Hbrv and Human Disordersmentioning
confidence: 99%
“…Ultimately, the activity of ART to reduce betaretrovirus load and improve biochemical and histological parameters of cholangitis in the NOD.c3c4 model [55] and in patients with PBC [55][56][57][58][59][60]66,67] can provide the consistency required for a causal association. Clinical trials using repurposed HIV antiretroviral regimens in PBC patients have consistently shown significant reduction in alkaline phosphatase levels indicative of biochemical improvement in cholangitis [55][56][57][58][59][60]66,67]. A proportion of these studies included liver biopsy assessment and revealed concurrent improvement in cholangitis and the inflammatory activity [57,58,66].…”
Section: Consistency Of the Association Between Hbrv And Pbcmentioning
confidence: 99%
See 3 more Smart Citations